Asians in east Africa - Delf, George (London, 1963)
This book portrays the present situation of the community of a quarter of a million Asians in East Africa. It considers past developments in so far as they help to explain the present dangers confronting this community, and then analyses recent trends and developments and the relations between the Asians and the other ethnic groups in the four East African territories. George Delf was brought up in India. After coming down from Cambridge in 1956 he went to Kenya, where he edited the English section of the Asian owned weekly Colonial Times in Nairobi. His biography of Jomo Kenyatta was published in 1961.
Keywords: Sociology